Using the UTAUT Model to Understand the Behavioral Intention to Use Mendeley Among Undergraduate Students of the Second Semester: Mixed Research Method - Muzammil, Ahmad Rabiul; Mariyadi, Mariyadi; Asfar, Dedy Ari (FKIP Universitas Lampung, 2024)
Abstract: Using the UTAUT Model to Understand the Behavioral Intention to Use Mendeley Among Undergraduate Students of the Second Semester: Mixed Research Method. Objective: This study aims to uncover the factors that influence behavioral intention to use Mendeley among second-semester students at Tanjungpura University using the Unified Theory of Acceptance and Use of Technology (UTAUT). Furthermore, this study deepens the findings of the UTAUT factors with qualitative research. Methods: This study utilised a mixed research method: quantitative-qualitative. Sixty students using the Mendeley application who were studying in the second semester at the Faculty of Engineering, Tanjungpura University, in 2023 became respondents in this study. Quantitatively, data were collected through a survey with the help of Google Form which was then analysed using the Partial Least Square Structural Equation Modeling (PLS-SEM) statistical testing method. Qualitatively, this study utilised open-ended interviews with selected students to explain the findings of the quantitative research. Findings: Based on SEM analysis, the factor that has a high influence on Behavioural Intention (BI) is Social Influence (SI) followed by Performance Expectancy (PE), and finally Effort Expectancy (EE). These findings are confirmed in qualitative research which reveals that the biggest influence of Mendeley adoption is environmental influence, namely encouragement from lecturers and from peers and the influence of the performance of the Mendeley application which helps citation and bibliography. Conclusion: This study concludes that students responded positively to the Mendeley application, perceived it as an application that can help write academic texts, easy to learn, and recognized that the factors of support from lecturers and peer influence as the main factors of the reasons for adoption. The low EE factor was caused by several usage problems experienced by students when connecting Mendeley and Microsoft Word which often caused errors. Keywords: RMS, mendeley, behavioral intention, UTAUT, mixed method.DOI: http://doi.org/10.23960/jpp.v14.i1.202441